I Diritti Fondamentali Come Limite Alla Política Criminale - Sorbello, Pietro (Revista Amagis Jurídica, 2024)
European Directive 2014/57/EU on criminal sanctions for market abuse and the “Grande Stevens” case of the European Court of Human Rights draws attention to the need to respect the fundamental right of double jeopardy ( ne bis in idem ). The foundation of fundamental rights inevitably affects the choices of criminal policy at all levels with the need, for the domestic law, to eliminate the duplication of sanctions and adapt the guarantees in proceedings for the imposition of sanctions formally administrative but criminal in substance, according to the Engel criteria. The direct applicability of the Charter of Fundamental Rights of the European Union provides advanced protection mechanisms directing the conduct of any legal practitioner.